Types of resistance of family farmers in the Northwest of Uruguay - Rossi Rodríguez, Virginia (2019)
Despite the advance of agrarian capitalism over the Pampas pastures, still most family farmers in Uruguay are livestock producers, dedicated to the mixed breeding of cattle and sheep. Within the framework of a more comprehensive investigation about resistance practices of family farming, concepts of Bourdieu's work are used, such as peasant habitus and practical sense, to analyze the resistance strategies of family farmers in northwestern Uruguay. An ethnographic study of sixteen families of livestock farmers, through the "Global Approach of Agricultural Exploitations" and life stories of families, allowed to identify the strategies (economic, educational, inheritance and symbolic), and typify the resistance of these family farmers. It is discussed the role of endogenous and exogenous conditions in the families' objectives and in the practices and strategies generated.